Method for removing uranium and organic matters in water body and simultaneously generating power

By using tin sulfide nanosheets/carbon felts as cathodes and titanium dioxide nanomaterial photovoltaic cells as anodes in the photoelectric catalytic reaction cell, the efficient removal of hexavalent uranium and organic matter in the water body is solved by using light to excite electrons and hole pairs. The problem is to realize the triple function of efficient removal and power generation.

CN119160982AActive Publication Date: 2024-12-20NANHUA UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411112013.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-20
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously remove hexavalent uranium and organic matter from water bodies and convert chemical energy in wastewater into clean energy, resulting in ecosystem threats and energy waste.

Method used

A single-chamber photoelectrocatalytic reaction cell is used, tin sulfide nanosheets/carbon felts are used as cathodes, and titanium dioxide nanomaterials and photovoltaic cells are used as composite photoanodes. The electron and hole pairs are excited by light illumination to improve the separation efficiency of electrons and holes. The selective adsorption and reducing properties of tin sulfide are used to reduce the activation barrier of uranium, and to achieve its efficient removal and degradation of organic matter, while generating electricity.

Benefits of technology

The removal rate of hexavalent uranium and organic matter has been achieved to reach more than 97%, and the maximum output power is 2.03mW·cm-2. It has triple functions: removal, degradation and power generation, with a wide range of applications, and can directly utilize sunlight without additional energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160982A_ABST
    Figure CN119160982A_ABST
Patent Text Reader

Abstract

The invention provides a method for removing uranium and organic matters in a water body and simultaneously generating power, and particularly relates to the field of resourceful treatment of wastewater. The method provided by the invention comprises the following steps: placing an electrolyte solution containing a hexavalent uranium source and an organic matter in a photoelectrocatalysis reaction tank for illumination; the photoelectric catalytic reaction tank takes a tin sulfide nanosheet / carbon felt as a cathode and takes a titanium dioxide nano material and a photovoltaic cell as a composite photo-anode. The photo-anode is excited by light to generate electron hole pairs, the rear photovoltaic cell is excited by light to generate bias voltage to drive photo-induced electrons to be transferred to the cathode and generate electricity, and meanwhile, the separation efficiency of the electrons and holes is improved; soluble hexavalent uranium easy to migrate is rapidly enriched by the tin sulfide nanosheet / carbon felt and is reduced into tetravalent uranium precipitation not easy to migrate on the surface of the tin sulfide nanosheet / carbon felt by photo-induced electrons and low-valence S. A test result shows that the highest removal rate of the method provided by the invention on the organic matters and uranium can reach 97% or above, and the maximum power density is 2.01 mW.cm <-2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resource-based wastewater treatment, and specifically relates to a method for removing uranium and organic matter from water and generating electricity simultaneously. Background Art

[0002] With the rapid development of industry, environmental pollution and resource shortage have become key issues that restrict human beings from achieving sustainable development. It is well known that organic wastewater contains huge chemical energy, and traditional treatment technology only considers its removal performance and ignores its chemical energy, resulting in energy waste. Therefore, the current pollution control method should focus on the conversion and utilization of energy, and achieve pollution control and energy production simultaneously, so as to promote the sustainable development of human society.

[0003] At present, the photoelectrocatalytic reaction system has attracted widespread attention from researchers as a method that can simultaneously degrade organic matter and produce clean energy. However, few organic pollutants exist alone in wastewater, and most organic pollutants coexist with heavy metals such as hexavalent uranium. Therefore, if only the degradation of organic matter and power generation are considered while ignoring the treatment of heavy metals such as hexavalent uranium, this type of wastewater will still pose a serious threat to the ecosystem. In the prior art, although the treatment methods for hexavalent uranium wastewater such as adsorption, solvent extraction, evaporation, chemical reduction and photocatalytic technology all show good treatment performance, they can rarely achieve efficient reduction of uranium (U) and efficient degradation of organic matter at the same time, and convert chemical energy into clean energy. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a method for removing uranium and organic matter from water and generating electricity at the same time, so as to solve the problem that the existing technology is difficult to simultaneously achieve efficient removal of metals and organic matter and convert chemical energy in wastewater into clean energy.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The present invention provides a method for removing uranium and organic matter from water and generating electricity simultaneously, comprising the following steps:

[0007] Placing an electrolyte solution containing a hexavalent uranium source and organic matter in a single-chamber photoelectrocatalytic reaction cell for illumination; the single-chamber photoelectrocatalytic reaction cell uses tin sulfide nanosheets / carbon felt as a cathode and titanium dioxide nanomaterials and photovoltaic cells as a composite photoanode;

[0008] The illumination condition is xenon lamp or sunlight.

[0009] Preferably, the electrolyte in the electrolyte solution includes one or more of sodium sulfate, potassium sulfate, magnesium sulfate and sodium chloride, and the concentration of the electrolyte is 0.05-1.0 mol / L.

[0010] Preferably, the preparation method of the tin sulfide nanosheets / carbon felt comprises:

[0011] dissolving a tin source and a sulfur source in water to obtain a mixed solution;

[0012] placing the carbon felt in the mixed solution and performing a hydrothermal reaction to obtain tin sulfide nanosheets / carbon felt;

[0013] The molar ratio of the tin source to the sulfur source is 0.25-0.55:1.

[0014] Preferably, the tin source is SnCl4;

[0015] The sulfur source is one or more of thiourea, thioacetamide and L-cysteine.

[0016] Preferably, the temperature of the hydrothermal reaction is 150-170° C., and the time is 8-16 hours.

[0017] Preferably, the hexavalent uranium source is uranyl nitrate hexahydrate, uranyl acetate dihydrate or uranyl carbonate;

[0018] Preferably, the organic matter includes one or more of antimicrobial agents, herbicides, antibiotics, anti-inflammatory agents, pesticides and intermediates.

[0019] Preferably, the concentration of the hexavalent uranium source is 5 to 12 mg / L;

[0020] The concentration of the organic matter is 5-12 mg / L.

[0021] Preferably, the pH value of the electrolyte solution is 4.0-5.5.

[0022] Preferably, the illumination time is 50 to 3600 min.

[0023] The present invention provides a method for removing uranium and organic matter from water and generating electricity at the same time, comprising the following steps: placing an electrolyte solution containing a hexavalent uranium source and organic matter in a single-chamber photoelectrocatalytic reaction cell for illumination; the single-chamber photoelectrocatalytic reaction cell uses tin sulfide nanosheets / carbon felt as a cathode, and titanium dioxide nanomaterials and photovoltaic cells as a composite photoanode; the illumination condition is a xenon lamp or sunlight. The present invention utilizes the photoanode to generate electron-hole pairs when excited by light, and the bias voltage generated by the rear photovoltaic cell when excited by light can drive the photogenerated electrons to transfer to the cathode and generate electricity, while improving the separation efficiency of electrons and holes. The holes and their derivatives ·OH left at the anode can degrade organic matter and break the organic matter and uranium (UO2 2+) releases hexavalent uranium through complexation, and then the soluble and easily mobile hexavalent uranium is quickly enriched by the tin sulfide nanosheets / carbon felt and reduced to non-mobile tetravalent uranium precipitate by photogenerated electrons and low-valent S on its surface; the tin sulfide nanosheets / carbon felt have a selective adsorption effect on uranium, in which sulfur, as a Lewis base, has a strong affinity for the Lewis acid UO2 2+ The ion has a strong affinity and can easily undergo chemical complexation reaction with it to form a complex, which reduces its activation barrier and makes it easy to be reduced by photogenerated electrons. At the same time, the low-valent S can also directly reduce hexavalent uranium to tetravalent uranium.

[0024] UO2 2+ With a trans-dioxygen-encapsulated U oxygen-containing cation structure, the electron transfer activation barrier is relatively high. Compared with hydrogen production or the reduction of other heavy metals such as Cr(VI) (Cr(VI) / Cr(III), 1.33V), UO2 2+ The reduction of ions is more difficult. Directly using the carbon felt in the existing photoelectrocatalytic system as the cathode may have problems such as low uranium removal effect and slow reaction rate, which will affect the separation efficiency of electrons and holes and the degradation of organic matter. The present invention uses hydrothermal reaction to grow nanosheet tin sulfide on the surface of carbon felt. The presence of tin sulfide significantly enhances the conductivity and interface charge transfer efficiency of carbon felt, strengthens the electrocatalytic activity of carbon felt, promotes uranium reduction and organic matter degradation, and has good stability and reusability.

[0025] Furthermore, the present invention constructs an optimized single-chamber photoelectrocatalytic reaction system by controlling and optimizing the preparation method of tin sulfide nanosheets / carbon felt, adjusting the pH of the electrolyte solution, the concentration of the hexavalent uranium source and organic matter, the electrolyte concentration and other parameters. The test results show that the method provided by the present invention for removing uranium and organic matter from water and generating electricity at the same time has a removal effect of more than 97% for each organic matter and uranium, and the maximum output power reaches 2.03mW·cm -2 , which can efficiently remove uranium and organic matter and generate electricity.

[0026] Compared with the prior art, the advantages of the present invention are: (1) using tin sulfide nanosheets / carbon felt that has adsorption and reduction properties for uranium as the cathode, a photoelectrocatalytic system that can efficiently remove uranium and organic matter and generate electricity is constructed; (2) it has triple functions. Compared with existing treatment methods such as adsorption and photocatalysis, which can only achieve single or dual functions, the technology provided by the present invention can simultaneously and efficiently remove uranium and organic matter and convert chemical energy in wastewater into electrical energy, and has higher application value; (3) it can directly use sunlight without the need for additional energy. Compared with the feature that the adsorption method requires additional power to stir it evenly, the method provided by the present invention can directly use actual light, without the need for additional energy to achieve the removal of uranium and organic matter and generate electricity; (4) it has a wide range of applications. For different types of organic matter + uranium wastewater, the removal rate is above 93.35%, and the maximum output power can reach up to 2.01mW·cm -2 (5) It can be quickly disassembled and reconstructed to timely recover and enrich uranium in wastewater. Compared with the conventional powder adsorbents and photocatalysts that are difficult to recover, the photoelectrocatalytic system provided by the present invention can be directly taken out for recycling. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0028] Figure 1 is the SEM image of the prepared tin sulfide nanosheet / carbon felt material;

[0029] Figure 2 is the BET diagram of the prepared tin sulfide nanosheet / carbon felt material;

[0030] Figure 3 This is the mapping diagram of the prepared tin sulfide nanosheet / carbon felt material;

[0031] Figure 4 This is the XPS image of the prepared tin sulfide nanosheet / carbon felt material;

[0032] Figure 5 CV graph of the prepared tin sulfide nanosheet / carbon felt material;

[0033] Figure 6 This is the EIS graph of the prepared tin sulfide nanosheet / carbon felt material;

[0034] Figure 7Figure 2 shows the removal effect of different organic matter and uranium (a) and the power generation performance (b) of a single-chamber photoelectrocatalytic reaction cell constructed with the prepared tin sulfide nanosheets / carbon felt material. DETAILED DESCRIPTION

[0035] The present invention provides a method for removing uranium and organic matter from water and generating electricity simultaneously, comprising the following steps:

[0036] Placing an electrolyte solution containing a hexavalent uranium source and organic matter in a single-chamber photoelectrocatalytic reaction cell for illumination; the single-chamber photoelectrocatalytic reaction cell uses tin sulfide nanosheets / carbon felt as a cathode and titanium dioxide nanomaterials and photovoltaic cells as a composite photoanode;

[0037] The illumination condition is xenon lamp or sunlight.

[0038] In the present invention, unless otherwise specified, the raw materials and equipment used are commercially available products well known in the art.

[0039] In the present invention, the hexavalent uranium source is preferably uranyl nitrate hexahydrate, uranyl acetate dihydrate or uranyl carbonate, more preferably uranyl nitrate hexahydrate. The concentration of the hexavalent uranium source is preferably 5-12 mg / L, more preferably 8-10 mg / L. In a specific embodiment of the present invention, the concentration of the hexavalent uranium source is 10 mg / L.

[0040] In the present invention, the organic matter preferably includes one or more of antibacterial agents, herbicides, antibiotics, anti-inflammatory agents, pesticides and intermediates. The antibacterial agent preferably includes a medium-acting sulfonamide, more preferably sulfadiazine; the antibiotic preferably includes a quinolone antibiotic or a tetracycline antibiotic, more preferably ciprofloxacin or tetracycline hydrochloride; the herbicide preferably includes a triazine herbicide, more preferably atrazine; the anti-inflammatory agent preferably includes a non-steroidal anti-inflammatory drug, more preferably ibuprofen; the pesticide and intermediate preferably include nitrophenol, more preferably p-nitrophenol. In the present invention, the concentration of the organic matter is preferably 5-12 mg / L, more preferably 8-10 mg / L, and the concentration of the organic matter in the specific embodiment of the present invention is 10 mg / L.

[0041] In the present invention, the electrolyte in the electrolyte solution preferably includes one or more of sodium sulfate, potassium sulfate, magnesium sulfate and sodium chloride, more preferably sodium sulfate, and the concentration of the electrolyte is preferably 0.05 to 1.0 mol / L, more preferably 0.1 to 0.5 mol / L. In a specific embodiment of the present invention, the concentration of sodium sulfate is 0.05 mol / L, 0.1 mol / L or 0.5 mol / L.

[0042] In the present invention, the pH value of the electrolyte solution containing the hexavalent uranium source and the organic matter is preferably 4.0 to 5.5, more preferably 4.1 to 5.2, and further preferably 4.5 to 5.0. In the present invention, the pH adjusting solution is preferably one or both of sulfuric acid and sodium hydroxide.

[0043] In the present invention, the tin sulfide nanosheets / carbon felt comprises carbon felt and tin sulfide nanosheets distributed on the surface of the carbon felt.

[0044] In the present invention, the preparation method of the tin sulfide nanosheets / carbon felt preferably comprises:

[0045] dissolving a tin source and a sulfur source in water to obtain a mixed solution;

[0046] placing the carbon felt in the mixed solution and performing a hydrothermal reaction to obtain tin sulfide nanosheets / carbon felt;

[0047] The molar ratio of the tin source to the sulfur source is 0.25-0.55:1.

[0048] In the present invention, the tin source is preferably SnCl4; the sulfur source is preferably one or more of thiourea, thioacetamide and L-cysteine, more preferably thiourea. In the present invention, the molar ratio of the tin source to the sulfur source is preferably 0.25-0.55:1, more preferably 0.3-0.5:1. In a specific embodiment of the present invention, the molar ratio of the tin source to the sulfur source is 0.4:1.

[0049] In the present invention, the concentration of the tin source in the mixed solution is preferably 0.2 to 0.4 mol / L.

[0050] In the present invention, the carbon felt is preferably pretreated before being placed in the mixed solution. The present invention has no special requirements for the pretreatment method, and a commonly used treatment method in the art can be used. Specifically, the carbon felt is ultrasonically cleaned with ultrapure water and ethanol in sequence and then dried.

[0051] The present invention has no special requirements on the size of the carbon felt. In an embodiment of the present invention, the size of the carbon felt is preferably 2.0×5.0 cm 2 The mass is 0.6 g. In the present invention, the amount of the mixed solution is preferably sufficient to completely immerse the carbon felt.

[0052] In the present invention, the temperature of the hydrothermal reaction is preferably 150-170° C., more preferably 155-165° C., and the time is preferably 8-16 hours, more preferably 10-13 hours. During the hydrothermal reaction, nano-sheet tin sulfide grows on the surface of the carbon felt.

[0053] After the hydrothermal reaction is completed, the present invention preferably further comprises cooling the obtained hydrothermal reaction product to room temperature, then washing with deionized water and ethanol respectively, and drying to obtain a tin sulfide nanosheet / carbon felt material.

[0054] In the present invention, the number of washing with deionized water and ethanol is preferably 2 to 3 times independently, the temperature of drying is preferably 60° C., and the time is preferably 12 hours.

[0055] In the present invention, the tin sulfide nanosheet / carbon felt has a selective adsorption effect on uranium, wherein sulfur acts as a Lewis base to adsorb UO2 2+ Ions have a strong affinity for UO2 2+ The ions undergo chemical complexation to form complexes, reducing UO2 2+ ions, making them easy to be reduced by photogenerated electrons; at the same time, the free S 2- You can also directly communicate with UO2 2+ A redox reaction occurs, reducing hexavalent uranium to UO2, which is fixed in the form of a precipitate. In addition, tin sulfide significantly enhances the electrical conductivity and interfacial charge transfer efficiency of carbon felt, strengthens the electrocatalytic activity of carbon felt, promotes the reduction of uranium and the degradation of organic matter, and has good stability and reusability.

[0056] In the present invention, the photoelectrocatalytic reaction cell is preferably a single-chamber photoelectrocatalytic reaction cell. The photoelectrocatalytic reaction cell uses tin sulfide nanosheets / carbon felt as a cathode and titanium dioxide nanomaterials and photovoltaic cells as a composite photoanode.

[0057] In the present invention, the titanium dioxide nanomaterial is preferably prepared by the commonly used technical means in the art. Specifically, a mixture containing 0.1 mL of tetrabutyl titanate (TBT) and 10 mL of ethanol is placed on a FTO (2×4 cm 2 ) was coated at 3000 rpm for about 30 seconds, dried at 60°C for 30 minutes, and annealed at 450°C for 2 hours. Subsequently, 30 mL of ultrapure water, 30 mL of hydrochloric acid (37 wt%), and 0.72 mL of TBT were mixed to prepare a precursor solution. The homogenized precursor solution was transferred to an autoclave, and the prepared FTO substrate was placed at the bottom with the TiO2 seed layer facing down. After heating at 170°C for 6 hours, the polytetrafluoroethylene autoclave was naturally cooled to room temperature, and the obtained TNR was calcined at 500°C for 2 hours.

[0058] In the present invention, the photovoltaic cell is preferably a silica gel cell.

[0059] In the present invention, the composite photoanode is obtained by combining titanium dioxide nanomaterials and silicone battery packs in a front-to-back stacking manner, and binding the edges of the two with a silicone rubber sealing strip, wherein the positive electrode of the silicone battery is directly connected to the TNR.

[0060] In the present invention, the composite photoanode of the titanium dioxide nanomaterial and the photovoltaic cell is excited by light, and under the excitation of short-wavelength light (<400nm), electron-hole pairs are generated, wherein the holes and their derivatives ·OH (hole h + Hydroxyl radicals H2O+h are generated by reacting with water in solution + → OH+H + ) can degrade organic matter, thereby breaking the complexation between organic matter and uranium to release hexavalent uranium. The bias voltage generated by the rear photovoltaic cell under the excitation of long-wavelength light waves (400nm~780nm) drives the photogenerated electrons to transfer to the cathode, reducing the hexavalent uranium enriched on its surface by tin sulfide and generating electricity.

[0061] In the present invention, the illumination condition is preferably a xenon lamp or sunlight, and the illumination time is preferably 50 to 3600 min, more preferably 60 to 3000 min; when a xenon lamp is used, the illumination intensity is preferably 85 to 120 mW·cm -2 , more preferably 100 mW·cm -2 The xenon lamp is preferably used in combination with a 1.5 filter (AM 1.5G), and the time is preferably 60 minutes; when sunlight is selected, the time is preferably 3600 minutes.

[0062] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described in conjunction with specific embodiments below. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Any modification, equivalent replacement, improvement, etc. made to the implementation methods of the present invention based on the technical essence and general principles of the present invention without creative work should be within the scope of protection of the present invention.

[0063] Preparation of tin sulfide nanosheets / carbon felt

[0064] Commercial carbon felt (2.0 × 5.0 cm) was ultrasonically cleaned with ultrapure water and ethanol. 2 ), dried at 60°C for 12h and set aside.

[0065] Add 5.47g (0.021mol) of tin tetrachloride and 3.9963g9 (0.053mol) of thiourea into 70mL of ultrapure water, dissolve and stir evenly, pour into a reactor containing clean commercial carbon felt, hydrothermally react at 160°C for 12h, cool to room temperature, wash with deionized water and ethanol for 2 to 3 times respectively, and dry at 60°C for 12h to obtain tin sulfide nanosheets / carbon felt material.

[0066] The obtained tin sulfide nanosheet / carbon felt material was observed under a scanning electron microscope, and its surface structure was as follows Figure 1 It can be observed that the surface of the carbon felt is rough and has a ball-like substance formed by nanosheets with an average length and average width of 0.5 μm and 0.05 μm respectively.

[0067] Figure 2 is the BET diagram of the prepared tin sulfide nanosheet / carbon felt material. Figure 2 It can be seen that the obtained nanosheet structure effectively increases the specific surface area of ​​the original carbon felt and provides more active sites for the carbon felt material.

[0068] The obtained tin sulfide nanosheet / carbon felt material was subjected to mapping test, and the test results are as follows: Figure 3 As shown, it can be seen that the tin sulfide in the tin sulfide nanosheet / carbon felt material is mainly composed of S and Sn.

[0069] The obtained tin sulfide nanosheet / carbon felt material was subjected to XPS test, and the test results are as follows: Figure 4 As shown. Analysis shows that the obtained tin sulfide nanosheet / carbon felt material contains Sn 4+ and S 2- , indicating that tin sulfide was successfully loaded onto the surface of carbon felt.

[0070] The original carbon felt and the tin sulfide nanosheet / carbon felt material were subjected to CV scanning. The results are as follows Figure 5 Compared with the original carbon felt, the current density on the CV curve of SnS nanosheets / carbon felt increased significantly.

[0071] Comparing the EIS results of the original carbon felt and the tin sulfide nanosheet / carbon felt material, Figure 6 It can be seen that the arc radius of tin sulfide nanosheets / carbon felt is smaller than that of the original carbon felt, which indicates that the carbon felt loaded with tin sulfide has a smaller resistance. This may be because the high conductivity of tin sulfide allows charges to be quickly transferred to the electrolyte through the substrate, thereby reducing the internal resistance of the entire electrochemical system, further indicating that the tin sulfide nanosheet / carbon felt material has fast charge transfer and good (photo) electrocatalytic performance.

[0072] Example 1

[0073] Using tin sulfide nanosheets / carbon felt as cathode, titanium dioxide nanomaterials + photovoltaic cells as composite photoanode, 0.568g sodium sulfate, 5mL 80mg / L uranyl nitrate and 5mL 80mg / L tetracycline hydrochloride were mixed with 30mL water to obtain a mixed solution, wherein the concentration of sodium sulfate was 0.1mol / L, the concentration of uranyl nitrate was 10mg / L, and the concentration of tetracycline hydrochloride was 10mg / L. The initial pH value of the mixed solution was adjusted to 5.03 and added to the reaction cell to construct a 3×4×5cm single-chamber photoelectrocatalytic reaction cell. A xenon lamp (AM 1.5G) was turned on at room temperature, and the photoanode in the prepared reaction cell was facing the light source and irradiated for 60min to complete the removal of uranium and tetracycline hydrochloride while generating electricity. The test results of the removal rate and maximum power density of uranium and tetracycline hydrochloride were collected and plotted as shown in Table 1 below.

[0074] Example 2

[0075] The other conditions were the same as those in Example 1, and the amount of sodium sulfate added was adjusted to 0.284 g to obtain a mixed solution containing 0.05 mol / L sodium sulfate. The test results are shown in Table 1

[0076] Example 3

[0077] The other conditions were the same as those in Example 1, and the amount of sodium sulfate added was adjusted to 2.84 g to obtain a mixed solution containing 0.5 mol / L sodium sulfate. The test results are shown in Table 1

[0078] Table 1 Removal effect and power generation of uranium and tetracycline hydrochloride in Examples 1 to 3

[0079]

[0080] As can be seen from Table 1, when the concentration of sodium sulfate gradually increases, the removal effect of uranium and tetracycline hydrochloride continues to increase, and the maximum output power density also continues to increase, mainly because the high concentration of sodium sulfate reduces the internal resistance of the solution and enhances the conductivity of the solution. When the concentration of sodium sulfate is 0.1M, the removal rates of uranium and organic matter reach 99.99% and 97.53%, and the pollutants are basically removed. The maximum output power density reaches 2.01mW·cm -2 ,As the sodium sulfate concentration continues to 0.5M, the removal rate and power production also increase, but considering the cost, 0.1M sodium sulfate concentration is selected.

[0081] Example 4

[0082] Other conditions were the same as those in Example 1. The initial pH value of the mixed solution was adjusted to 4.15. The test results are shown in Table 2.

[0083] Table 2 Removal effect and power generation of uranium and tetracycline hydrochloride in Examples 1 and 4

[0084]

[0085] It can be seen from Table 2 that when the initial pH value of the solution is 4.15, the removal rates of uranium and organic matter are 90.09% and 94.65%, respectively; as the pH increases to 5.03, the removal rates of uranium and tetracycline hydrochloride increase to 99.99% and 97.53%, respectively. This may be because as the pH increases, the removal rate of H + As the concentration decreases, there is less H + The uranium removal rate increases significantly due to the competition with uranium for photogenerated electrons. The increase in uranium removal rate means that more electrons are consumed, which further enhances the separation efficiency of electrons and holes, and more separated holes are available for the degradation of organic matter, thus increasing the efficiency of organic matter.

[0086] Example 5

[0087] Other conditions were the same as those in Example 1, and the initial concentration of tetracycline hydrochloride was adjusted to 5 mg / L. The test results are shown in Table 3.

[0088] Table 3 Removal effect and power generation of uranium and tetracycline hydrochloride in Examples 1 and 5

[0089]

[0090] It can be seen from Table 3 that when the concentration of tetracycline hydrochloride solution is reduced to 5 mg / L, the removal rate of uranium and tetracycline hydrochloride and the power output remain at a high level. The removal rate of tetracycline hydrochloride and can reach 97.65% and 98.34% respectively, and the maximum output power density reaches 2.03 mW cm -2 .

[0091] Example 6

[0092] Other conditions were the same as those in Example 1. The initial concentration of the uranium solution was adjusted to 5 mg / L. The test results are shown in Table 4.

[0093] Table 4 Removal effect and power generation of uranium and tetracycline hydrochloride in Examples 1 and 6

[0094]

[0095] It can be seen from Table 4 that when the concentration of uranium solution is reduced to 5 mg / L, the removal rate of uranium and tetracycline hydrochloride and the power generation still remain at a high level.

[0096] Comparative Example 1

[0097] Other conditions were the same as those in Example 1. The cathode of the single-chamber photoelectrocatalytic reaction cell was adjusted to the cleaned carbon felt. The test results are shown in Table 5.

[0098] Table 5 Removal effect and power generation of uranium and tetracycline hydrochloride in Example 1 and Comparative Example 1

[0099]

[0100] It can be seen from Table 5 that the removal efficiency of uranium and tetracycline hydrochloride in the single-chamber photoelectrocatalytic reaction cell constructed by using the cleaned commercial carbon felt as the cathode is 29.34% and 54.35%, which is much lower than the removal efficiency of uranium (99.99%) and tetracycline hydrochloride (97.53%) under the same conditions in Example 1, and its maximum output power density (1.11 mW·cm -2 ) is also much lower than the maximum output power density (2.01 mW cm) of a single-chamber photoelectrocatalytic reaction cell with tin sulfide nanosheets / carbon felt as the cathode. -2 ). It was confirmed that the tin sulfide nanosheets / carbon felt improved the electrocatalytic activity of the photoelectrocatalytic reaction system.

[0101] Comparative Example 2

[0102] The obtained tin sulfide nanosheet / carbon felt material was used as an adsorbent and added to a mixed solution of 40 mL containing 0.568 g sodium sulfate (0.1 mol / L), 10 mg / L uranyl nitrate and 10 mg / L tetracycline hydrochloride. The pH was adjusted to 5.03 and adsorbed for 60 minutes to complete the removal of uranium and tetracycline hydrochloride. The test results are shown in Table 6.

[0103] Comparative Example 3

[0104] Titanium dioxide nanomaterials were used as photocatalysts and added into a 40 mL mixed solution containing 0.568 g sodium sulfate (0.1 mol / L), 10 mg / L uranyl nitrate and 10 mg / L tetracycline hydrochloride. The pH was adjusted to 5.03 and the solution was irradiated at room temperature for 60 min under a xenon lamp (AM1.5G) to remove uranium and tetracycline hydrochloride. The test results are shown in Table 6.

[0105] Table 6 Test results of removal efficiency of uranium and tetracycline hydrochloride in Example 1 and Comparative Examples 2-3

[0106]

[0107] As shown in Table 6, when the tin sulfide nanosheets / carbon felt alone is used as the adsorbent, the removal rates of uranium and tetracycline hydrochloride are 47.66% and 51.60%, respectively, which are much lower than the photoelectrocatalytic system constructed with it as the cathode, and uranium is still enriched on the surface of the material in the form of hexavalent uranium or molecular form, which has a greater migration risk. When the titanium dioxide nanomaterial alone is used as the photocatalyst, the removal rates of uranium and tetracycline hydrochloride are 19.00% and 8.05%, respectively, which are much lower than the photoelectrocatalytic system constructed with it as the anode.

[0108] Application Example 1

[0109] Other conditions were the same as those in Example 1. The xenon lamp in Example 1 was replaced with sunlight, and the irradiation time was adjusted to 3600 min. The removal of uranium and tetracycline hydrochloride was completed and electricity was generated simultaneously. The test results are shown in Table 7.

[0110] Table 7 Removal effect and power generation of uranium and tetracycline hydrochloride in Example 1 and Application Example 1

[0111]

[0112] As shown in Table 7, under actual illumination, the removal rates of uranium and tetracycline hydrochloride in the single-chamber photoelectrocatalytic reaction cell constructed with tin sulfide modified carbon felt as the cathode reached 92.49% and 97.96%, respectively, and the maximum output power density reached 44.78 mW·cm -2 It can be seen that the method provided by the present invention can achieve efficient removal of uranium and tetracycline hydrochloride in water and stable power generation by relying solely on sunlight without consuming other energy sources.

[0113] Application Example 2

[0114] Other conditions are the same as those in Example 1, except that tetracycline hydrochloride in Example 1 is replaced with p-nitrophenol, ciprofloxacin, atrazine, ibuprofen or sulfadiazine. The test results are shown in 8.

[0115] Table 8 Removal effect and power generation of uranium and tetracycline hydrochloride in Example 1 and Application Example 2

[0116]

[0117] As shown in Table 8, the removal efficiency of organic matter and uranium in the single-chamber photoelectrocatalytic reaction cell constructed with tin sulfide nanosheets / carbon felt as cathode reached more than 93.35%, and the maximum output power reached 2.01 mW·cm -2 , which can efficiently remove uranium and organic matter and generate electricity.

[0118] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for removing uranium and organic matter from water and generating electricity simultaneously, characterized in that: The following steps are involved: Placing an electrolyte solution containing a hexavalent uranium source and organic matter in a single-chamber photoelectrocatalytic reaction cell for illumination; the single-chamber photoelectrocatalytic reaction cell uses tin sulfide nanosheets / carbon felt as a cathode and titanium dioxide nanomaterials and photovoltaic cells as a composite photoanode; The illumination condition is xenon lamp or sunlight.

2. The method according to claim 1, characterized in that The electrolyte in the electrolyte solution includes one or more of sodium sulfate, potassium sulfate, magnesium sulfate and sodium chloride, and the concentration of the electrolyte is 0.05-1.0 mol / L.

3. The method according to claim 1, characterized in that The preparation method of the tin sulfide nanosheet / carbon felt comprises: dissolving a tin source and a sulfur source in water to obtain a mixed solution; placing the carbon felt in the mixed solution and performing a hydrothermal reaction to obtain tin sulfide nanosheets / carbon felt; The molar ratio of the tin source to the sulfur source is 0.25-0.55:

1.

4. The method according to claim 3, characterized in that The tin source is SnCl4; The sulfur source is one or more of thiourea, thioacetamide and L-cysteine.

5. The method according to claim 3, characterized in that: The temperature of the hydrothermal reaction is 150-170° C. and the time is 8-16 hours.

6. The method according to claim 1, characterized in that The hexavalent uranium source is uranyl nitrate hexahydrate, uranyl acetate dihydrate or uranyl carbonate.

7. The method according to claim 1, characterized in that The organic matter includes one or more of antimicrobial agents, herbicides, antibiotics, anti-inflammatory agents, pesticides and intermediates.

8. The method according to claim 1 or 6, characterized in that: The concentration of the hexavalent uranium source is 5 to 12 mg / L; The concentration of the organic matter is 5-12 mg / L.

9. The method according to claim 1 or 2, characterized in that: The pH value of the electrolyte solution is 4.0-5.

5.

10. The method according to claim 1, characterized in that The illumination time is 50 to 3600 minutes.

Citation Information

Patent Citations

  • Device and method for extracting uranium from uranium-containing wastewater or seawater and application thereof

    CN112342385A

  • MOF (Metal Organic Framework) derived carbon nanotube / carbon matrix composite material as well as preparation method and application thereof

    CN115945208A

  • Etching carbon material and preparation method and application thereof

    CN117684388A

  • Photoelectrochemical(PEC) device Comprising CIGS Photovoltaic-Photoelectrode Tandem Configuration

    KR1020210092503A

  • Hood release lever assembly and mounting structure of the same

    KR1020230011809A